2018
DOI: 10.1007/s11547-018-0886-3
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular canal branching assessed with cone beam computed tomography

Abstract: Mandibular canal branching presented a high prevalence in CBCT imagery, more frequently located in regions of the premolar and retromolar. An adequate diagnosis of the MCB is necessary to perform dental procedures and verify possible associated pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…As a recurrent tumor in the vicinity of the mandibular canal has been misdiagnosed, this knowledge will also encourage extra care when dealing with clinical uncertainty (Guimaraes, Pontes, Mata Rezende Ddos, & Pontes, 2014). Added to this problem is the recent finding that tomographic images of pathologies and BMCs often coexist in the molar region (de Castro et al, 2018).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…As a recurrent tumor in the vicinity of the mandibular canal has been misdiagnosed, this knowledge will also encourage extra care when dealing with clinical uncertainty (Guimaraes, Pontes, Mata Rezende Ddos, & Pontes, 2014). Added to this problem is the recent finding that tomographic images of pathologies and BMCs often coexist in the molar region (de Castro et al, 2018).…”
Section: Diagnosismentioning
confidence: 99%
“…CT and CBCT have been used to overcome the limitations of panoramic radiography (Fukami et al, ). So far, four studies have used both panoramic and CBCT (López‐Videla et al, ; Moro et al, ; Muinelo‐Lorenzo et al, ; Neves et al, ), two have used a combination of CT and CBCT (Rouas, Delbos, & Nancy, ; Shen et al, ), 21 have used only CBCT, one of them determining the prevalence of BMC in children (Afsa & Rahmati, ; Borgonovo et al, ; de Castro et al, ; de Oliveira‐Santos et al, ; Kang et al, ; Kuribayashi et al, ; Li et al, ; Luangchana et al, ; Naitoh et al, ; Neves et al, ; Ogawa et al, ; Okumu & Dumlu, ; Orhan et al, ; Orhan et al, ; Rashsuren et al, ; Shah et al, ; Sonneveld et al, ; Villa et al, ; Yang et al, ; Yi et al, ; Yoon et al, ; Zhang et al, ), and two have used only CT (Fu et al, ; Lins et al, ). These CT and CBCT studies reported a higher prevalence of BMC, in the range 0.05 to 69.0% (Table ).…”
Section: Bifid Mandibular Canalmentioning
confidence: 99%
See 1 more Smart Citation
“…De Castro et al assessed mandibular canal branching (MCB) with CBCT and concluded that the prevalence of MCB was 41.1%, among which 61.5% presented one branch; nevertheless, 38.5% presented more than one MCB. There was no statistically significant difference in gender regarding the presence of MCB or the pattern of presence (i.e., single branch or multiple branches) (11). Okumus et al demonstrated BMCs in 200 (40%) of the 500 subjects and in 248 of the 1000 sides (24.8%) (12).…”
Section: Discussionmentioning
confidence: 94%
“…Second, since the IAN travels in various directions in 3D, it is difficult to intuitively determine the exact shape [ 16 ]. Thirdly, it is difficult to determine whether the shape or position of the nerve has been deformed due to adjacent teeth or lesions [ 17 ]. Finally, if the cortical layer of the mandibular canal surrounding the IAN is unclear from the image, it is difficult to determine the exact location [ 18 ].…”
Section: Discussionmentioning
confidence: 99%